MODELING CURRENT SYSTEM IN SOUTH VIET NAM WATERS- GULF OF THAILAND - Dương, Phạm Xuân (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents some results of the study on circulation regime of the South Vietnam waters-Gulf of Thailand during northeast monsoon (dry season) and southwest monsoon (rainy season) by ROMS model. Parameters of meteorological, tide, radiation, evaporation were taken from the global ocean data (resolution of ¼ degrees). The study results showed that during northeast monsoon, it’s appeared the currents along the coast of South Vietnam waters from northeast to southwest. They pour into the Gulf of Thailand with high frequencies, and push the coastal flows into the middle areas of Gulf. By this aspect, the flow field in the Gulf of Thailand forms a closed cycle in the upper area from latitude 90N at many moments. During the southwest monsoon, this phenomenon is also appears, but lower frequency, and the direction of flow from southwest to northeast.